AP4 deficiency: A novel form of neurodegeneration with brain iron accumulation?. (February 2018) - Roubertie, Agathe; Hieu, Nelson; Roux, Charles-Joris; Leboucq, Nicolas; Manes, Gael; Charif, Majida; Echenne, Bernard; Goizet, Cyril; Guissart, Claire; Meyer, Pierre; Marelli, Cecilia; Rivier, François; et al.
Abstract : Objective: To describe the clinico-radiological phenotype of 3 patients harboring a homozygous novel AP4M1 pathogenic mutation. Methods: The 3 patients from an inbred family who exhibited early-onset developmental delay, tetraparesis, juvenile motor function deterioration, and intellectual deficiency were investigated by magnetic brain imaging using T1-weighted, T2-weighted, T2*-weighted, fluid-attenuated inversion recovery, susceptibility weighted imaging (SWI) sequences. Whole-exome sequencing was performed on the 3 patients. Results: In the 3 patients, brain imaging identified the same pattern of bilateral SWI hyposignal of the globus pallidus, concordant with iron accumulation. A novel homozygous nonsense mutation was identified in AP4M1, segregating with the disease and leading to truncation of half of the adap domain of the protein. Conclusions: Our results suggest that AP4M1 represents a new candidate gene that should be considered in the neurodegeneration with brain iron accumulation (NBIA) spectrum of disorders and highlight the intersections between hereditary spastic paraplegia and NBIA clinical presentations.